Building on Progress Expanding the Research Infrastructure for the Social, Economic, and Behavioral Sciences (e3149f5d-0687-402f-8178-f149dcbd140b, 2011)
This publication provides a comprehensive compendium of the current state of Germany's research infrastructure in the social, economic, and behavioural sciences. In addition, the book presents detailed discussions of the current needs of empirical researchers in these fields as well as of opportunities for future development. The importance of solid data for both public policy and the social and economic sciences is obvious. Today, empirical research is essential in finding solutions to many of the major challenges our society faces, such as environmental change, turbulent financial markets, and population growth. Based on 68 advisory reports by more than 100 internationally recognised authors from a wide range of fields, the book provides recommendations by the German Data Forum (RatSWD) on how to improve the research infrastructure so as to create conditions ideal for making Germany's social, economic, and behavioural sciences more innovative and internationally competitive.